Blue Economy Based Fisheries and Marine Business Model Development - Rini, Ayu Dwidyah; Handy, Silvester Dian; Hidayah, Isnawati (Jurnal Entrepreneur dan Entrepreneurship, 2021)
This study aims to develop blue economy based business model and develop a blue economy based information system about fisheries and marine resources in 60 (sixty) areas of KIMBis (Fish Innovation and Business Development Clinic) in Brebes Regency. The methodology used is a research-based design (DBR) which consisted of eight stages of development. Based on the development and discussion results, the canvas business model developed can create advantages in the KIMBis fisheries and marine business; (a) efficient fishery production activities through a polyculture system and integrated with agricultural activities. (2) The creation of new fisheries marketing channels that support efficiency and reduce the domination of middlemen’s role. (3) Diversification of fishery products includes new product variants at low prices and environmentally friendly. (4) Environmentally friendly fishery and marine businesses. The information system in the form of a website developed can provide information related to the company profile, which contains the Vision, Mission of KIMBis, products sold, product stock-taking, ordering and purchasing via connected WhatsApp, membership, and business contacts.